Hypoxia modulates the activity of a series of clinically approved tyrosine kinase inhibitors. (January 2014) - Ahmadi, M; Ahmadihosseini, Z; Allison, S J; Begum, S; Rockley, K; Sadiq, M; Chintamaneni, S; Lokwani, R; Hughes, N; Phillips, R M
<x xml:space="preserve">Abstract</x> Background and Purpose Hypoxia in tumours is known to cause resistance to conventional chemotherapeutic drugs. In contrast, little is known about the effects of hypoxia on targeted anti‐cancer drugs. This study evaluated the effect of hypoxia on a series of clinically approved tyrosine kinase inhibitors (TKIs). Experimental Approach The effect of hypoxia (0.1% oxygen) on the activity of conventional cytotoxic drugs (5‐fluorouracil, doxorubicin and vinblastine), the hypoxia‐activated prodrug tirapazamine and 9 TKIs was determined in a panel of cell lines. Where hypoxia had a marked effect on chemosensitivity, Western blot analysis was conducted to determine the effect of hypoxia on target expression and the effect of TKIs on cell signalling response under aerobic and hypoxic conditions. Key Results Three patterns of chemosensitivity were observed: resistance under hypoxia, equitoxic activity against hypoxic and aerobic cells, and preferential cytotoxicity to hypoxic cells. Significant hypoxia selectivity (independent of HIF1) was observed in the case of dasatinib and this correlated with the ability of dasatinib to inhibit phosphorylation of Src at tyrosine 530. Sorafenib was significantly less effective under hypoxic conditions but resistance did not correlate with hypoxia‐induced changes in Raf/MEK/ERK signalling. Conclusions and Implications Hypoxia influences the activity of TKIs but in contrast to conventional cytotoxic drugs, preferential activity against hypoxic cells can occur. The search for hypoxia‐targeted therapies has been long and fruitless and this study suggests that some clinically approved TKIs could preferentially target the hypoxic fraction of some tumour types.